ChemInform Abstract: Reagent Controlled β‐Specific Dehydrative Glycosylation Reactions with 2‐Deoxy‐sugars. Issue 2 (14th January 2014) - Issa, John Paul; Lloyd, Dina; Steliotes, Emily; Bennett, Clay S.
Abstract It is demonstrated that 2‐deoxysugar hemiacetals react with 1‐tosyl‐4‐nitroimidazol to generate intermediates which react with S‐ or O‐nucleophiles to give β‐glycosides exclusively.